Draft Fourth Five Year Plan October 1966 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1966)
Uttar Pradesh, with 17 per cent of the population of the country, is the largest State. The pace of development during the past three Plan periods has, however, been almost the slowest in the country. This is not surprising in view of the low levels of investment which have been made in Uttar Pradesh. It has been estimated that dining the first two Plan periods, the total investment in Uttar Pradesh, as a percentage of total investment in India, was only 7.2. In the Third Plan period the level of investment was a little less than 10 percent of the total in the country. A per capita investment of about hall the all India average could hardly result in the rate of growth of the economy being anywhere near the all-India average.
Government of Uttar Pradesh, Planning Department